Research on the Influence of Circulating Cooling Water on Electrochemical Scale Inhibition. Issue 5 (May 2020) - Geng, Man; Zhong, Shaotao; Wang, Guangwu; Cui, Pengfei; Chen, Dingsheng
Abstract: Electrochemical water treatment technology can effectively prevent the formation of scales. In this paper, the electrochemical workstation is used to explore the process of cathode scale formation and its influencing factors under different conditions. The results show that the electrochemical scale inhibition can effectively remove Ca 2 + and Mg 2 + in water. When it comes to scale inhibition, and it provides theoretical analysis and experimental basis for solving the scaling problem of the external cold spray water of the high-voltage DC valve cooling system.